Histology and histochemistry of the albumin glands in some foam-nesting anurans - Alcaide, MaríaF. (2009)
This study deals with the histology and histochemistry of the oviducts of three species of frogs that lay their eggs embedded in a foam nest (Leiuperidae: Physalaemus biligonigerus and Pleurodema borellii; Leptodactylidae: Leptodactylus chaquensis). In all of them the oviducts show five sections [in cephalic-caudal direction, the Pars Recta (PR), Intermediate Proximal Zone (IPZ), Preconvolute Part (PCP), Convolute Part (CP) and Ovisac (O)] identifiable on anatomical and histological basis, and on the peculiarities of their secretions and joined biomolecules. In the section encompassed between the distal portion of PPC and O of the three species it was possible to identify glandular areas that produce glycoconjugates with a dominance of proteins joined to lipids or to glucids that constitute the precursor of the foam. These histologically differentiated glandular aggregations, not yet recorded in species with other modes of oviposition, are named here as “albumin glands”.